Investigating the vision of AI driven website builder in user interface components (Jóvenes en la Ciencia, 2024)
This study investigates the transformative potential of AI-driven website builders in revolutionizing the creation and optimization of user interface (UI) components. Through a systematic exploration of AI-based prompts, the study scrutinizes the efficacy of these platforms in generating UI elements across varying levels of complexity. Seven distinct UI components, including dropdowns, checkboxes, and alerts, were subjected to rigorous scrutiny through prompts issued to an AI-driven website builder. The results shed light on the AI's ability to comprehend and execute user queries, revealing nuanced insights into its proficiency in generating relevant and accurate UI elements. While the AI demonstrated commendable performance in handling complex queries, challenges emerged in achieving precision with simpler components. The findings underscore the importance of continued refinement and enhancement of AI algorithms to ensure accuracy and relevance in UI component generation, thus contributing to the ongoing evolution of web development practices.